Sarcocystis caninum and Sarcocystis svanai n. spp. (Apicomplexa: Sarcocystidae) Associated with Severe Myositis and Hepatitis in the Domestic Dog (Canis familiaris) - Dubey, Jitender P; Sykes, Jane E; Shelton, G Diane; Sharp, Nick; Verma, Shiv K; Calero‐Bernal, Rafael; Viviano, Jenifer; Sundar, Natarajan; Khan, Asis; Grigg, Michael E (eScholarship, University of California, 2015)
There are several reports of Sarcocystis sarcocysts in muscles of dogs, but these species have not been named. Additionally, there are two reports of Sarcocystis neurona in dogs. Here, we propose two new names, Sarcocystis caninum, and Sarcocystis svanai for sarcocysts associated with clinical muscular sarcocystosis in four domestic dogs (Canis familiaris), one each from Montana and Colorado in the USA, and two from British Columbia, Canada. Only the sarcocyst stage was identified. Most of the sarcocysts identified were S. caninum. Sarcocysts were studied using light microscopy, transmission electron microscopy (TEM), and polymerase chain reaction. Based on collective results two new species, S. caninum and S. svanai were designated. Sarcocystis caninum and S. svanai were structurally distinct. Sarcocystis caninum sarcocysts were up to 1.2 mm long and up to 75 μm wide. By light microscopy, the sarcocyst wall was relatively thin and smooth. By TEM, the sarcocyst wall was "type 9", 1-2 μm thick, and contained villar protrusions that lacked microtubules. Bradyzoites in sections were 7-9 μm long. Sarcocysts of S. svanai were few and were identified by TEM. Sarcocystis svanai sarcocysts were "type 1", thin walled (< 0.5 μm), and the wall lacked villar protrusions but had tiny blebs that did not invaginate. DNA was extracted either from infected frozen muscle biopsies or formalin-fixed paraffin-embedded sections. Dogs were either singly infected with S. caninum or multiply co-infected with S. caninum and S. svanai (the result of a mixed infection) based on multilocus DNA sequencing and morphology. BLASTn analysis established that the sarcocysts identified in these dogs were similar to, but not identical to Sarcocystis canis or Sarcocystis arctosi, parasites found to infect polar bears (Ursus maritimus) or brown bears (Ursus arctosi), respectively. However, the S. caninum sequence showed 100% identify over the 18S rRNA region sequenced to that of S. arctica, a parasite known to infect Arctic foxes (Vulpes lagopus).